Electrocatalytic activity and electrochemical stability of Ni–S/CeO2 composite electrode for hydrogen evolution in alkaline water electrolysis. (28th December 2016) - Zhang, Kaiyue; Li, Junyao; Liu, Weihua; Liu, Jianguo; Yan, Chuanwei
Abstract: In this study, Ni–S/CeO2 composite electrodes with different content of micro-CeO2 or nano-CeO2 particles have been prepared by composite electrodeposition onto nickel foam substrates. The composite deposition processes mainly include three stages: initial stage, accelerating stage and steady stage. The embedded CeO2 particles enlarge the surface area of electrodes. And the possible synergetic effects resulted from the interactions between CeO2 and the Ni–S alloy enhances the hydrogen evolution reaction (HER). Compared with micro-CeO2 particles, nano-CeO2 particles are difficult to be embedded in the matrix. However, the HER electrocatalytic activity of nano-CeO2 composite electrodes is generally higher than that of micro-CeO2 composite electrodes related to the uniform distribution of embedded nano-CeO2 particles on the electrodes. The HER electrocatalytic activity is not simply proportional to the content of embedded CeO2 particles. It is found that the addition of CeO2 enhances the impact resistance of electrodes and reduces the dissolution of active element S, so the composite electrodes provide a higher electrochemical stability. Highlights: The Ni–S/CeO2 composite electrodes with high S content are prepared. The composite deposition processes are revealed. The nano-CeO2 composite electrodes can provide high HER activity. HER activity is not simply proportional to the Ce content. The addition of CeO2 particles can increase electrochemical stability.